Intellectual Capital Performance, Prestasi Reputasi Perusahaan dan Financial Distress - Setiawan, Ilham; Yurniwati, Yurniwati; Putri, Anne (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
The company's going concern ability should be able to compete and survive in business activities to avoid financial distress. This study aims to determine the effect of intellectual capital performance, company achievement, company reputation, profitability, and leverage on financial distress. This study uses samples from manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample used was 125 observations taken using purposive sampling technique. Data analysis was performed using logistic regression analysis. The results showed that the performance of intellectual capital and profitability had a negative effect on financial distress and leverage had a positive effect on financial distress. Meanwhile, company achievement and company reputation have no effect on financial distress. Keywords: Intellectual Capital Performance; Company Achievement; Company Reputation; Financial Distress.